La mobilisation des ressources publique au Brésil après la Constitution Fédérale de 1988 - Araújo Ribeiro, Rodrigo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The work wehave before usis toexploreadvancedfinancial activityof the democratic stateunder Brazilian law, afterthe promulgation of the1988 Constitution, and thecreation ofopportunitiesinstitutesof popular participationinthe TaxPublic Administration.
Keywords: The financial activities of the Brazilian state; The Federal Constitution of 1988; Institutes of popular participation of the Brazilian Public Administration; Participatory Budget; Simplification Committee and Revision of Tax Legislation